Linking changes in the soil microbial community to C and N dynamics during crop residue decomposition - Cyrine REZGUI; Isabelle TRINSOUTROT-GATTIN; Marie BENOIT; Karine LAVAL; Wassila RIAH-ANGLET (Journal of Integrative Agriculture)
Crop residues are among the main inputs that allow the organic carbon (C) and nutrients to be maintained in agricultural soil. It is an important management strategy that can improve soil fertility and enhance agricultural productivity. This work aims to evaluate the extent of the changes that may occur in the soil heterotrophic microbial communities involved in organic matter decomposition and C and nitrogen (N) mineralization after the addition of crop residues. Soil microcosm experiments were performed at 28°C for 90 days with the addition of three crop residues with contrasting biochemical qualities: pea (Pisum sativum L.), rapeseed (Brassica napus L.), and wheat (Triticum aestivum L.). Enzyme activities, C and N mineralization, and bacterial and fungal biomasses were monitored, along with the bacterial and fungal community composition, by the high-throughput sequencing of 16S rRNA and ITS genes. The addition of crop residues caused decreases in β-glucosidase and arylamidase activities and simultaneous enhancement of the C mineralization and net N immobilization, which were linked to changes in the soil microbial communities. The addition of crop residues decreased the bacterial and fungal biomasses 90 days after treatment and there were shifts in bacterial and fungal diversity at the phyla, order, and genera levels. Some specific orders and genera were dependent on crop residue type. For example, Chloroflexales, Inquilinus, Rubricoccus, Clitocybe, and Verticillium were identified in soils with pea residues; whereas Thermoanaerobacterales, Thermacetogenum, and Hypoxylon were enriched in soils with rapeseed residues, and Halanaerobiales, Rubrobacter, and Volutella were only present in soils with wheat residues. The findings of this study suggest that soil C and N dynamics in the presence of the crop residues were driven by the selection of specific bacterial and fungal decomposers linked to the biochemical qualities of the crop residues. If crop residue decomposition processes showed specific bacterial and fungal operational taxonomic unit (OTU) signatures, this study also suggests a strong functional redundancy that exists among soil microbial communities.